Long‐Term Safety ofIn UteroExposure to Anti‐TNFα Drugs for the Treatment of Inflammatory Bowel Disease: Results from the Multicenter European TEDDY Study. (March 2018) - Chaparro, M; Verreth, A; Lobaton, T; Gravito‐Soares, E; Julsgaard, M; Savarino, E; Magro, F; Biron, Avni I; Lopez‐Serrano, P; Casanova, M J; Gompertz, M; Vitor, S; et al.
Abstract : OBJECTIVES: The long‐term safety of exposure to anti‐tumor necrosis factor (anti‐TNFα) drugs during pregnancy has received little attention. We aimed to compare the relative risk of severe infections in children of mothers with inflammatory bowel disease (IBD) who were exposed to anti‐TNFα drugs in utero with that of children who were not exposed to the drugs. METHODS: Retrospective multicenter cohort study. Exposed cohort: children from mothers with IBD receiving anti‐TNFα medication (with or without thiopurines) at any time during pregnancy or during the 3 months before conception. Non‐exposed cohort: children from mothers with IBD not treated with anti‐TNFα agents or thiopurines at any time during pregnancy or the 3 months before conception. The cumulative incidence of severe infections after birth was estimated using Kaplan–Meier curves, which were compared using the log‐rank test. Cox‐regression analysis was performed to identify potential predictive factors for severe infections in the offspring. RESULTS: The study population comprised 841 children, of whom 388 (46%) had been exposed to anti‐TNFα agents. Median follow‐up after delivery was 47 months in the exposed group and 68 months in the non‐exposed group. Both univariate and multivariate analysis showed the incidence rate of severe infections to be similar in non‐exposed and exposed children (1.6% vs. 2.8% per person‐year, hazard ratio 1.2 (95% confidence interval 0.8–1.8)). In the multivariate analysis, preterm delivery was the only variable associated with a higher risk of severe infection (2.5% (1.5–4.3)). CONCLUSIONS: In utero exposure to anti‐TNFα drugs does not seem to be associated with increased short‐term or long‐term risk of severe infections in children.